Causes and outcomes of emergency presentation of rectal cancer. Issue 5 (5th May 2016) - Comber, Harry; Sharp, Linda; de Camargo Cancela, Marianna; Haase, Trutz; Johnson, Howard; Pratschke, Jonathan
Abstract : Emergency presentation of rectal cancer carries a relatively poor prognosis, but the roles and interactions of causative factors remain unclear. We describe an innovative statistical approach which distinguishes between direct and indirect effects of a number of contextual, patient and tumour factors on emergency presentation and outcome of rectal cancer. All patients diagnosed with rectal cancer in Ireland 2004–2008 were included. Registry information, linked to hospital discharge data, provided data on patient demographics, comorbidity and health insurance; population density and deprivation of area of residence; tumour type, site, grade and stage; treatment type and optimality; and emergency presentation and hospital caseload. Data were modelled using a structural equation model with a discrete‐time survival outcome, allowing us to estimate direct and mediated effects of the above factors on hazard, and their inter‐relationships. Two thousand seven hundred and fifty patients were included in the analysis. Around 12% had emergency presentations, which increased hazard by 80%. Affluence, private patient status and being married reduced hazard indirectly by reducing emergency presentation. Older patients had more emergency presentations, while married patients, private patients or those living in less deprived areas had fewer than expected. Patients presenting as an emergency were less likely to receive optimal treatment or to have this in a high caseload hospital. Apart from stage, emergency admission was the strongest determinant of poor survival. The factors contributing to emergency admission in this study are similar to those associated with diagnostic delay. The socio‐economic gradient found suggests that patient education and earlier access to endoscopic investigation for public patients could reduce emergency presentation. Abstract : What's New? Regardless of cancer stage, emergency admission for rectal cancer carries a higher death rate than planned admission. To understand what leads to emergency presentation, these authors devised a new statistical technique to distinguish direct and indirect effects of various factors, including possession of private insurance, age and marital status. The factors that contributed to emergency presentation are similar to those that cause a delay in diagnosis: age, poverty, marital status. Thus, they conclude, patient education and improved access to screening for patients on public insurance would reduce the number of emergency admissions.